The Role of Vascular Imaging to Advance Clinical Care and Research in Large-Vessel Vasculitis - Quinn, Kaitlin A. (Curr Treatm Opt Rheumatol, 2019)
PURPOSE OF THE REVIEW: The two main forms of large-vessel vasculitis (LVV) are giant cell arteritis (GCA) and Takayasu’s arteritis (TAK). Vascular imaging can characterize disease activity and disease extent in LVV. This review critically analyzes the clinical utility of vascular imaging in LVV and highlights how imaging may be incorporated into the management and study of these conditions. RECENT FINDINGS: There are multiple imaging modalities available to assess LVV including ultrasonography, CT angiography (CTA), magnetic resonance angiography (MRA), and (18)F-fluorodeoxyglucose (FDG) positron emission tomography (PET). As these techniques are refined, imaging may be increasingly useful to evaluate the cranial arteries and the aorta and its primary branches. In addition, vascular imaging may be useful to monitor disease activity and may have prognostic value to predict future clinical events. SUMMARY: There are strengths and weaknesses associated with vascular imaging that should be considered when evaluating patients with LVV. Vascular imaging will likely play an increasingly important role in the clinical management of patients and the conduct of research in LVV and may ultimately be incorporated as outcome measures in clinical trials in these conditions.